Patient care issues after carotid artery reperfusion procedure - Wawszczak, Emilia; Lewandowska, Marzena; Kądalska, Ewa (Nursing Problems / Problemy Pielęgniarstwa, 2016)
Introduction. Carotid artery reperfusion is a procedure applied in case of atherosclerotic stricture thereof, and one of the prophylaxis methods that aims at preventing cerebral infarction. An effectively performed endarterectomy procedure allows to improve the patient’s life quality in a visible manner. Regarding the risk of complications during the post-operative care, a nurse is required to present broad knowledge and extensible skills, guaranteeing immediate intervention and avoidance of conditions, which may endanger the patient’s life and health. Purpose. Purpose of the work was to analyze care issues pertaining to a patient, who underwent an endarterectomy procedure, and to suggest available solutions. Material and methods. The research was performed on a patient, who was hospitalized on the Vascular Surgery Department in Warsaw, in order to undergo surgical treatment as a result of the medical diagnosis - 85% stricture of the right internal carotid artery. The patient expressed a consent for the performed research. The individual case study method was applied. The following research techniques were adopted: survey questionnaire with the patient, their family, medical personnel, analysis of medical documentation and direct observation in the early and late post-operative period. Conclusions. The plan of the perioperative care over the patient considered the most significant and the most frequently encountered care issues in patients after a surgery of carotid artery reperfusion. Nursery care over the patient, who undergoes an endarterectomy procedure, should be of a holistic nature.